The Impacts of COVID-19 on Business Practice: Some Key Insights - Sooreea, Rajeev; Sooreea, Brinda (Advances in Social Sciences Research Journal, 2022)
This paper provides an overview of some of the key economic impacts of COVID-19 on business practice, especially in the U.S. In particular, we synthesize some of the latest research, findings and developments from various academic literature and business sources to provide a managerial perspective of the effects of this pandemic. In addition, we show some characteristics of the so-called “new normal” and what kind of innovative business opportunities could arise as a result of the fundamental changes in the global economy. We conclude by highlighting how some emerging countries like India could tap into such opportunities despite the dire global situation.